Estudo comparativo entre os modelos de controle externo do Brasil x Argentina - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The study was conducted in order to verify and compare the operation of the external control models Brazil and Argentina, analyzing the Federal Audit Court - TCU and General Audit of the Nation - AGN respectively, for these two countries are presented as the major economies of MERCOSUL and the two main economies of South America, which increases the importance of understanding how these two bodies and his relationship with the democratic system in both countries. But the theoretical framework was constructed through the modern literature on the subject, and especially through the analysis of legislation seeking to prove the historical evolution of the models in each country and describe in our times to work the two entities within the peculiarities of each model. For this a comparative analysis of external control models in the two countries was held, demonstrating that both the formation of the federation (centripetal or centrifugal modeling) and hybridization of the models was a key issue for contemporary formation of the ones analyzed.
Comparative study between Brazil x Argentina external control models
Keywords: Tribunal de contas da União; Gestão pública; Controle externo; Auditoria general de la nación; Federal Audit Court; Public administration; External control; CNPQ::CIENCIAS SOCIAIS APLICADAS